Floating solar sustainability on land and ocean: A strategic assessment using SWOT-TWOS-PESTLE analysis - Kaur, Nisha; Sudhakar, K.; Mohd Rusllim, Mohamed; Cuce, Erdem; Barbulescu, Dan (Editions Technip, 2025)
Floating Solar Projects (FSP) offer a revolutionary approach to harnessing solar energy, with the potential to address land-use constraints and tap into the expansive resources both on land and ocean surfaces. This paper conducts a comparative analysis of land-based and ocean-based Floating Solar PhotoVoltaic (FSPV) deployments using SWOT (Strengths, Weaknesses, Opportunities, and Threats), TOWS (a strategic approach based on SWOT), and PESTLE (Political, Economic, Social, Technological, Legal, and Environmental) analysis. We identify the unique strengths and weaknesses of each approach, such as land-based FSP’s easier implementation versus ocean-based FSP’s potential for large-scale generation. The TOWS matrix further develops strategic options for leveraging these differences, while the PESTLE analysis assesses the political, economic, social, technological, legal, and environmental factors that will shape the success of each deployment. Additionally, the analysis highlights the abundance of opportunities for FSPV systems, particularly in terms of policy and economic support, contributions to Sustainable Development Goals (SDGs), and technological advancements. This comprehensive assessment provides critical insights for stakeholders aiming to implement FSPV strategically, driving the transition toward a sustainable energy future.